BIBLIOMETRIC ANALYSIS OF RESEARCH TREND ON AGILE IT GOVERNANCE - Antonius Sony Eko Nugroho; Viany Utami Tjhin; Wibowo Kosasih; Harjanto Prabowo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This paper was prepared to analyze the scientific trends of research on Agile IT Governance through bibliometric studies in the Scopus and Google Scholar databases. From the search results using Publish or Perish in 2016 to 2021, samples were obtained consisting of 132 documents in the Scopus database and 962 documents in the Google Scholar database. The results of querying five years of data showed that scientific publications on Agile IT Governance had increased significantly since 2016. Based on the Scopus database, researchers from Germany contributed the most documents on Agile IT Governance. Still, the number of citations was dominated by the UK for research on this topic. Then, the visualization of research trends on Agile IT Governance also resulted in four clusters of co-occurrence from Scopus and Google Scholar, which lead into some topic areas mentioned in the result; 1) Agile IT Governance management in the world, 2) Agile IT Governance in relating to digital innovation and digital transformation, 3) Agile IT Governance in implementing technological and environmental innovations, and 4) Agile IT Governance in relating to its effect and benefit to society. The findings in this study will undoubtedly help related researchers recognize trends in Agile IT Governance research globally and recommend directions for further research in the future. Keywords: Agile, IT Governance, Bibliometric Study, Research Trend, VOSviewer